The Role of International Organizations in the Globalization of the Economy and its Impact on National Sovereignty - Norouzi, Nima; Ataei, Elham (Journal of Economic and Business Law Review, 2023)
The end of World War II was the beginning of expanding organized international relations and the growth of relations between different nations in all areas, especially the trade of goods and services. The spread of these connections led to a phenomenon called globalization. Globalization is tied to freedom of trade and competition. Its requirements so far have been that governments have been forced to largely change their laws, regulations, policies, and policies to enter this field and to accept various international requirements and commitments. The activities of international organizations, both global and regional, have intensified this trend. Globalization has changed the definitive boundary between domestic and international affairs, and the process of globalization has transformed the traditional concepts and structure of governance and the relationship between governance and law. The territorial jurisdiction of countries has been severely pressured by the globalization of the economy and social relations. In this transformation, the authority of all countries, both strong and weak, has been lost due to integration into the world economy.